Pengembangan Kompetensi Aparatur Perencana (Studi Kasus di Badan Perencanaan dan Pembangunan Daerah Provinsi Kalimantan Barat) - Amarullah, Dimas; Mardiyono, Mardiyono; Hermawan, Romy (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
The method of this research using qualitative approach. This research aims to explain the competency development efforts of apparatus undertaken by Regional Development and Planning Department of West Kalimantan Province Government as well as analyze the supporting factor and the restricting factors of competence development efforts. The research results indicate that Regional Development and Planning Department of West Kalimantan Province Government has been doing the competency development efforts through three study methods, namely education, training and development. The supporting factors of competence development efforts are high motivation of apparatus and the clarity of career level. While the restricting factors of competence development efforts are the lack of leader commitment, the lack of apparatus placement system, and the coordination between related department has not been going well.